Social Factors Influence Behavior in the Novel Object Recognition Task in a Mouse Model of Down Syndrome - Sierra, Cesar; De Toma, Ilario; Cascio, Lorenzo Lo; Vegas, Esteban; Dierssen, Mara (Frontiers in Behavioral Neuroscience, 2021)
The use of mouse models has revolutionized the field of Down syndrome (DS), increasing our knowledge about neuropathology and helping to propose new therapies for cognitive impairment. However, concerns about the reproducibility of results in mice, and their translatability to humans have become a major issue, and controlling for moderators of behavior is essential. Social and environmental factors, the experience of the researcher and the sex and strain of the animals can all have effects on behavior, and their impact on DS mouse models has not been explored. Here we analyzed the influence of a number of social and environmental factors, usually not taken into consideration, on the behavior of male and female wild type and trisomic mice (the Ts65Dn model), in one of the most used tests for proving drug effects on memory, the Novel Object Recognition Test (NOR). Using principal component analysis and correlation matrices we show that the ratio of trisomic mice in the cage, the experience of the experimenter, and the timing of the test have a differential impact on male and female and on wild type and trisomic behavior. We conclude that although the NOR test is quite robust and less susceptible to environmental influences than expected, to obtain useful results, the phenotype expression must be contrasted against the influences of social and environmental factors.